2020
DOI: 10.1080/03007995.2020.1754186
|View full text |Cite
|
Sign up to set email alerts
|

Real-world 2-year treatment patterns among patients with psoriatic arthritis treated with injectable biologic therapies

Abstract: Objectives: To assess long-term (2-year) biologic treatment patterns of psoriatic arthritis (PsA) patients who initiated adalimumab, certolizumab pegol, etanercept, golimumab, or ustekinumab. Methods: Adult patients with !1 pharmacy or medical claim for injectable PsA biologics (index date) were identified from the Optum's Clinformatics Data Mart (1 January 2013-31 December 2016). Adherence, persistence, post-discontinuation treatment patterns, and addition of adjunctive medications were evaluated by index bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In this real-world study of commercially insured patients with PsA, those who initiated an IL-12/ 23i had significantly longer treatment persistence, a lower discontinuation rate, and higher treatment adherence compared to patients who initiated either a TNFi or a tsDMARD during 1 year of follow-up. As expected, the magnitude of difference between medication classes varied according to the definitions of allowable gaps, but the pattern of higher persistence and adherence with IL12/23i than TNFi and tsDMARD was observed throughout both the main analysis and the sensitivity analyses [8,9]. Persistence and adherence were similar between IL-12/23 and IL-17i with most outcomes, but a minority of persistence outcomes favored IL-12/ 23i.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this real-world study of commercially insured patients with PsA, those who initiated an IL-12/ 23i had significantly longer treatment persistence, a lower discontinuation rate, and higher treatment adherence compared to patients who initiated either a TNFi or a tsDMARD during 1 year of follow-up. As expected, the magnitude of difference between medication classes varied according to the definitions of allowable gaps, but the pattern of higher persistence and adherence with IL12/23i than TNFi and tsDMARD was observed throughout both the main analysis and the sensitivity analyses [8,9]. Persistence and adherence were similar between IL-12/23 and IL-17i with most outcomes, but a minority of persistence outcomes favored IL-12/ 23i.…”
Section: Discussionsupporting
confidence: 59%
“…These findings are similar to other studies conducted over the past several years, in which discontinuation rates within 1 year of treatment initiation ranged from 33% to nearly 70% among PsA patients treated with biologics or other advanced therapies [ 5 , 6 , 8 , 10 , 11 ]. Furthermore, in a study of patients with PsA treated with injectable biologic drugs (adalimumab, certolizumab pegol, etanercept, golimumab, or ustekinumab), the overall discontinuation rate within 2 years of initiation was approximately 80% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study did not evaluate persistence beyond 12 months, previous research has shown that persistence rates decrease with time. Walsh et al reported a decrease in persistence rate from 44.5% after 12 months [25] to 19.7% after 24 months [27] of follow-up. A change in persistence rate after an even longer period of time was reported by Jacob et al [15] (from 71.4% after 12 months to 33.2% after 60 months of follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…8 9 Although biological agents are effective in treating PsA, 10 approximately 25%-40% of patients do not achieve at least 20% improvement in American College of Rheumatology score (ACR20), and clinical REM and minimal disease activity (MDA) are often short-lived. [11][12][13][14][15][16][17][18][19] Lack of efficacy frequently leads to treatment switching or discontinuation, which may negatively affect patients' clinical outcomes and increase treatment costs, [20][21][22][23][24] revealing a need for well-tolerated treatments with sustained efficacy.…”
Section: Psoriatic Arthritismentioning
confidence: 99%